RANCANG BANGUN PENYEBARAN INFORMASI LOWONGAN PEKERJAAN BERBASIS WEBSIDE (STUDI KASUS MAHASISWA DAN ALUMNI UNWAHA) (SAINTEKBU, 2022)
Job vacancy are important information needed by college graduates, especially UNWAHA students to get a job so as to improve the family economy. But information about the Job vacancy and its specifications are scattered and not centralized causing college graduates feeling difficult to access them. To overcome this, there needs to be a platform that can accommodate those information that will make it easier for graduates to find a job through information that is centralized on the job opening website and can recommend job openings that match the skills that graduates have. This website-based application uses, MySql and PHP. Codeigniter 3  Framework  in the development of website-based application compatibility with better hosting integration, making it suitable in website development